Corporate Portfolio of the Oil and Gas Production Enterprise - Lenkova, Olga Viktorovna (International Journal of Economics and Financial Issues, 2016)
This article offers a methodological approach to the analysis of a corporate business portfolio of the oil and gas production company. The sequence of steps for the implementation of analytical procedures is denoted. The choice of one of the traditional instruments of portfolio analysis – GE/McKinsey matrix – as a basis for the transformation (adaptation) is justified. Modification is carried out in relation to filling these tools with specific criteria and designation of borderline values of indicators at the demarcation of the portfolio into quadrants (sectors). At the same time, various sets of performance indicators are suggested for the evaluation of domestic and foreign projects in the portfolio. The results of testing the authors' recommendations on the example of a major Russian vertically integrated oil and gas company are provided. On the basis of analysis of the company's portfolio in the “Production” direction, general recommendations for its development in the context of domestic and foreign projects are given. Keywords: Corporate business portfolio, portfolio analysis, oil and gas company, oil production JEL Classifications: J44, M14